ISOLATION AND IDENTIFICATION OF DEGRADING BACTERIA MICROPLASTICS ON THE SURFACE WATER IN BAGANSIAPIAPI WATERS, RIAU PROVINCE - Wulandari, Aprilia; Nursyirwani, Nursyirwani; Feliatra, Feliatra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Microplastic pollution in the marine environment seriously threatens aquatic ecosystems, including in the coastal areas of Bagansiapiapi, Riau Province. This study aims to isolate and identify microplastic-degrading bacteria from the sea surface and test their degradation ability. Sampling was carried out at three different locations in the Bagansiapiapi waters, and then isolation, morphological identification, and biochemical tests were carried out at the Marine Microbiology Laboratory, Universitas Riau. Microplastic degradation tests using LDPE plastic were carried out for 30 days, and molecular identification was carried out using the 16S rRNA PCR method. The results showed significant differences in the number of bacteria between stations. Station I (port area) showed the highest bacterial density of 31.8 × 10⁴ CFU/ml. Six of the 14 bacterial isolates obtained showed the ability to degrade microplastics, with ISL 14 (Bacillus sp.) showing the highest degradation percentage of 30.38%. This finding shows the potential for utilizing local bacteria as bioremediation agents for microplastics in the marine environment effectively and environmentally friendly